MODEL PENGOLAHAN LIMBAH MENUJU ENVIRONMENTAL FRIENDLY PRODUCT - Moechamad Nasir (Benefit: Jurnal Manajemen dan Bisnis, 2012)
This research aim to build awareness of small entrepreneur in known central industriesnamily in Krajan, Mojosongo, and Jebres Solo in throwing away waste result of produce. The benefitof this research is similar of behavior of environmental consciousness collectively that is betweenpublics and entrepreneur to realize area balance. Population of Research that is small entrepreneur inindustrial sentra known in Krajan, Mojosongo, Jebres. Data collecting method by the way of indepthinterview entangles two keyperson that is owner and plant lessee. The Result of research showedexistence of industrial sentra known triggers a number of consequences and appearance a number ofrisk opportunities, that is from smallest to the biggest threat is destruction of environment. Findingresult of indepth interview indicates the importance of building awareness model of behavior inthrowing away waste result of produce with emphasis on general behavior theory.